ANALISIS PENERAPAN AKUNTANSI TERHADAP PROGRAM TANGGUNGJAWAB SOSIAL PERUSAHAAN DAN DAMPAKNYA TERHADAP PERUSAHAAN (Studi Kasus Pada PT. PELINDO III KUPANG): indonesia - Apriano Moises Seran; Maryono (Jurnal Akuntansi Universitas Muhammadiyah Kupang, 2023)
This study aims to determine how the calculation of the Balance Scorecard method in calculating inpatient service rates and to determine the difference in the amount of inpatient service rates between the rates set by the hospital and the calculation of the Balance Scorecard method. This type of research is comparative descriptive. The type of data used is quantitative data. The data sources in this study are primary data and secondary data. Data collection techniques in this study were observation, interviews and documentation. Analysis of the data used is descriptive analysis. The results of the study show as follows: a). Financial Perspective for calculating inpatient rates using the Balance Scorecard compared to the rates set by the hospital, the results of inpatient service rates are smaller with difference for VIP Class Rp.204.440,59, Class I Rp.104.930,36 and Class II Rp.25.219,79, while Class III the Balance Scorecard rate is higher than the Hospital rate of Rp.+30,646.01. So that the financial perspective can be categorized as good. B). Customer perspective in patient care services (customers) is categorized as good with a cost rate of Rp.120.736,51. C). Internal Business Process Perspective shows less growth results for BTO, BOR, TOI, and ALOS because they do not match the ideal value. While the GDR and NDR showed good results because they matched the ideal value. D). Learning and Growth Perspective for the value of employee retention shows good category results because the number of employees who leave 4% and are still relatively small